Looking to the past to see the future: mother–child future talk following memory sharing in three cultural communities - Koh, Jessie Bee Kim; Wang, Qi (Frontiers in Psychology, 2025)
The present study examined mother–child spontaneous future talk following memory sharing in three cultural communities. Seventy-one European American, 60 Chinese American, and 58 mainland Chinese mothers and their 3-year-old children discussed two past events at home, one positive and one negative. Chinese and Chinese American mothers and children were more likely than European American mothers and children to spontaneously engage in future talk following memory sharing. After discussing negative past events, Chinese and Chinese American mothers and children were more likely than European American mothers and children to engage in didactic talk that emphasized children’s adherence to moral standards, social norms, and behavioral expectations in the future. Conversely, European American mothers were more likely than the two groups of Chinese mothers to engage in autonomous talk that emphasized children’s preferences and opinions regarding the future. Findings are discussed in light of the influence of mother–child conversations as a cultural context on the development of mental time travel and a temporally extended self.